Pengaruh Gaya Kepemimpinan, Efektivitas Sistem Pengendalian Internal dan Budaya Tri Hita Karana Terhadap Kecurangan (Fraud) Akuntansi - Ni Putu Tarimas Yulia Putri; I Putu Deddy Samtika Putra (UNHI Press, 2023)
Indonesia is a country that is still developing, where fraud is growing very fast. Fraud is an act that is carried out intentionally to gain unfair or unlawful advantages by using deception with the aim of obtaining unfair or unlawful profits (IAPI, 2012). This study aims to determine the effect of Leadership Style, Internal Control System Effectiveness and Tri Hita Karana Culture on Accounting Fraud (Case Study in LPD in Ubud District). The population in this study were all LPD employees in Ubud District, totaling 32 LPD, consisting of 378 employees. Samples in this study were 91 employees who were determined by purposive sampling technique and tested using multiple linear regression analysis techniques. The results of this study indicate that leadership style has a negative and significant effect on accounting fraud. The effectiveness of the internal control system has a negative and significant effect on accounting fraud. Tri hita karana culture has a negative and significant effect on accounting fraud.